Okkasionalismus - Schubert, Katrin (WSK Band 6 (Wörterbücher zur Sprach- und Kommunikationswissenschaft): Text- und Diskurslinguistik.)

Neologismus - Schubert, Katrin (WSK Band 6 (Wörterbücher zur Sprach- und Kommunikationswissenschaft): Text- und Diskurslinguistik.)

Archaismus - Schubert, Katrin (WSK Band 6 (Wörterbücher zur Sprach- und Kommunikationswissenschaft): Text- und Diskurslinguistik.)

An emerging theory of loyalty program dynamics - Kim, Jisu J.; Steinhoff, Lena; Palmatier, Robert W. (Journal of the Academy of Marketing Science)
Keywords: Marketing; Economics and Econometrics; Business and International Management

 Zeitschrift für Romanische Sprachen und ihre Didaktik

Wide-Band Frequency Synthesizer with Ultra-Low Phase Noise Using an Optical Clock Source - Bahmanian, Meysam; Fard, Saeed; Koppelmann, Bastian; Scheytt, Christoph (2020 IEEE/MTT-S International Microwave Symposium (IMS))
This paper presents an ultra-wideband and ultra-low noise frequency synthesizer using a mode-locked laser as its reference. The frequency synthesizer can lock in the frequency range from 2 GHz to 20 GHz on any harmonic of a mode-locked laser optical pulse train. The integrated rms-jitter (1 kHz-100 MHz) of the synthesizer is less than 5 fs in the frequency range from 4 GHz to 20 GHz with a typical value of 4 fs and a minimum of 3 fs. This is the first reported wideband phase locked loop achieving sub-10 fs rms-jitter for offset frequencies larger than 1 kHz.

Interferometric method for determining the losses of spatially multi-mode nonlinear waveguides based on second harmonic generation. - Santandrea, Matteo; Stefszky, Michael; Roeland, Ganaël; Silberhorn, Christine (Optics Express)
The characterisation of loss in optical waveguides is essential in understanding the performance of these devices and their limitations. Whilst interferometric-based methods generally provide the best results for low-loss waveguides, they are almost exclusively used to provide characterization in cases where the waveguide is spatially single-mode. Here, we introduce a Fabry-Pérot-based scheme to estimate the losses of a nonlinear (birefringent or quasi-phase matched) waveguide at a wavelength where it is multi-mode. The method involves measuring the generated second harmonic power as the pump wavelength is scanned over the phase matching region. Furthermore, it is shown that this method allows one to infer the losses of different second harmonic spatial modes by scanning the pump field over the separated phase matching spectra. By fitting the measured phase matching spectra from different titanium indiffused lithium niobate waveguides to the model presented in this paper, it is shown that one can estimate the second harmonic losses of a single spatial-mode, at wavelengths where the waveguides are spatially multi-mode.
Keywords: Atomic and Molecular Physics; and Optics

Lesekompetenz fördern. Ein Manual für das LIFE-Programm zur Stärkung der Zusammenarbeit von Schule und Elternhaus - Bonanati, Sabrina; Greiner, Christian; Gruchel, Nicole; Buhl, Heike M.

Do Shy Children Behave Differently than Non-shy Children in a Long-term Child-robot Interaction? - Tolksdorf, Nils Frederik; Viertel, Fanziska; Rohlfing, Katharina J. (Companion of the 2020 ACM/IEEE International Conference on Human-Robot Interaction)

Parents’ Views on Using Social Robots for Language Learning - Tolksdorf, Nils Frederik; Rohlfing, Katharina J. (2020 29th IEEE International Conference on Robot and Human Interactive Communication (RO-MAN))